(untitled) (Journal of the College of Basic Education, 2024)
This research aims to give a clear picture of the general trend of extreme temperatures in Baghdad during the period (1992-2022) by analyzing data for the daily maximum temperature from the meteorological station in Baghdad. The results showed that the general trend of heat waves is increasing, especially in recent years. During the duration of the study, the study area was exposed to (152) heat waves distributed over the summer months. Long heat waves were the most frequent in the study area. July witnessed the most frequent heat waves, as the number of short heat waves reached (14), and the total number of medium heat waves reached ( 18) waves and the number of long waves reached (25) waves. The study area witnessed a noticeable increase in the number of heat waves in the third period (2013-2022), where the number of heat waves reached (50) waves, at a rate of (40%).